Human footprint : everything you will eat, use, wear, buy, and throw out in your lifetime - Kirk, Ellen (Author) (National Geographic, 2010)
"What's your human footprint? Well, it's 13,056 pints of milk; 28,433 showers; 12,888 oranges; 14,518 candy bars; 43,371 cans of soda; and $52,972 worth of clothes, all in one lifetime. And that's just a fraction of the mountain of stuff you'll consume. Think of that times six billion other footprints. Makes you want to step more lightly on the Earth!"--P. [4] of cover.